INTERNASIONALISASI PENDIDIKAN DAN STRATEGI PENGEMBANGAN ‘MODERNISASI’ PERGURUAN TINGGI AGAMA ISLAM DI INDONESIA - Muhammad Thoyib (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2011)
Abstrak Internasionalisasi pendidikan tinggi ke depan bukanlah suatu ironi. Tetapi realitas kekinian yang sudah semakin mengarahkan probability itu menjadi suatu kenyataan yang tanpa batas. Eksistensi dan suksesi perguruan tinggi di era liberalisasi ke depan sangat ditentukan oleh kuatnya kesiapan akademis dan kematangan infrastrukturnya untuk menjadi lebih „modern‟. Indonesia yang didukung oleh PTAI yang begitu besar haruslah menyiapkan perangkat kompetitif pendidikan tinggi Islam sedini mungkin sehingga ke depan PTAI di Indonesia memiliki good governonce system pendidikan tinggi yang unggul sehingga mampu berkompetisi di level nasional, bahkan internasional tanpa kehilangan Islamic morality character sebagai dasar aplikasinya. Asumsi itu setidaknya harus didukung oleh strategi pengembangan mutu sistem pendidikan tinggi Islam yang lebih baik; Pertama, manajemen pendidikan tinggi di perguruan tinggi agama Islam harus mampu berorientasi pada pengembangan mutu akademik berskala internasional sehingga academic and social needs untuk skala nasional dan regional sudah secara otomatis mampu dipenuhi. Kedua, aplikasi manajemen mutu harus didukung oleh good academic atmosphere sehingga upaya peningkatan mutu akademik dapat berjalan lebih cepat dan efektif. Ketiga, humanistic sense of diversity harus menjadi primary supporting PTAI dalam rangka internasionalisasi pendidikan Islam yang lebih humanis dan international academic networking yang luas untuk mendukung SDM dalam negeri menjadi lebih unggul, inovatif dan produktif. Kata kunci: Internasionalisasi Pendidikan, Strategi, dan PTAI Abstract The internationalization of higher education in the next time will not be an irony. But the reality of becoming chance had been directing it to the probability more faster to be reality without limits. The existence and success of higher education in the globalization era and liberalization of education in the future will be decided so much by the seatle of akademic and educational infrastructures preparation of the higher education. Indonesia that supporting by many Islamic higher educations (PTAI) should prepare its sets of competitive Islamic higher education equipment as early as possible for facing the future that Islamic higher education in Indonesia will has good governonce system of higher education to compete at national, more farther at international competition level without lossing Islamic morality character as its basic aplication. Supporting by established academic more better, the prospect of Islamic higher education in Indonesia, on the context of internationalization of education era will be able to survive for the next future. The asumtion also has to be supported by more better strategies for developing quality system of Islamic higher education; first, management of higher education at Islamic higher education (PTAI) should be able to concentrate for international academic quality development, so then the academic and social needs for national and regional level automatically derived. Second, aplication of quality management should be supported by good academic atmosphere implemented on the whole stakeholder’s commitment for achieving more better quality of Islamic higher education in the next future. Third, humanistic sense of diversity has to becoming primary supporting tool for Islamic higher education to face internationalization aplication more humanistic and large international academic networking for supporting Indonesia’s human resources becoming qualified, productive, inovative and competitive in all competition scales. Keywords: Internationalizaion of education, Strategy, and Islamic Higher Education